Mechano-chemical calcium waves in systems with immobile buffers (Archives of Mechanics - Test, 2008)
We study the existence of travelling waves of the free cytosolic calcium concentration in the presence of immobile buffers. We also take into account the mechanochemical interaction. In the proof we use the a priori estimates for solutions of systems with diffusing buffers and pass to zero with their diffusion coefficients.